Influence of training mini-basketball in the first year of training at the level of the physical health of children 6-7 years - Olena Mitova; Viola Onischenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to analyze the contemporary state of early specialization in sport, to find out its positive and negative influence on children`s organism on the basis of scientific and methodological literature, and also to carry out the control of the level of the health of the children aged 6-7 years old before training and after the first year of playing mini-basketball. Material and Methods: the study involved 60 children aged 6-7 years old, 22 - girls and 38 - boys, who were engaged in a section of mini-basketball in Sports Children and Youth Olympic school №5 in Dnipropetrovsk during 2013/2014 used the following research methods: theoretical analysis and compilation of scientific and methodical literature and the Internet, the method of analysis of documentary materials, pedagogical supervision, monitoring physical health of rapid assessment Apanasenko (1992), the method of mathematical statistics. Results: there was defined the level of physical health (according to rapid assessment by Apanasenko (1992)) of the children aged 6-7 years old before and after the first year of mini-basketball training. Conclusion: the results of our study confirm the experts opinion that nonsufficient level of the physical health of children aged 6-7 years old before going in for sport and insignificant increase in performance after the first year of playing mini-basketball is related not only to the deterioration of environmental and socio-economic conditions of modern society but also to significant deficiencies in the sports training of children of different ages, which no longer meets the requirements of the present time and needs to be improved